1987
DOI: 10.1128/aac.31.9.1332
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cefamandole and cefuroxime activity against oxacillin-resistant Staphylococcus epidermidis and oxacillin resistance phenotype

Abstract: The activity of cefamandole and cefuroxime against oxacillin-resistant Staphylococcus epidermidis was studied in vitro to determine whether there was any relationship between oxacillin resistance phenotypes and cephalosporin activity. Oxacillin resistance phenotypes were determined by efficiency-of-plating studies on Mueller-Hinton agar containing oxacillin, with and without NaCl, and incubated at 30 and 35°C. On the basis of MIC and MBC determinations, cefamandole was more active than cefuroxime against oxaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…We do not know whether the bacteria were killed, and it remains a possibility that there was later regrowth. Nevertheless, better in vitro bactericidal activity for cefamandole than for cefazolin and cefuroxime has been demonstrated by other investigators (12,16,17).…”
Section: Discussionmentioning
confidence: 96%
“…We do not know whether the bacteria were killed, and it remains a possibility that there was later regrowth. Nevertheless, better in vitro bactericidal activity for cefamandole than for cefazolin and cefuroxime has been demonstrated by other investigators (12,16,17).…”
Section: Discussionmentioning
confidence: 96%
“…MBCs in salt-supplemented MHB were greater than or equal to those in unsupplemented MHB. We do not know why salt supplementation resulted in such a marked change of the MBC; however, a similar effect has been observed with cefuroxime against oxacillin-resistant S. epidermidis (18). The condition.…”
mentioning
confidence: 99%
“…Because the effects of 2% NaCl and temperature on the MBCs of oxacillin against such strains had not been examined, for each strain the MCB was determined under four conditions: in MHB with and without 2% NaCl supplementation and incubation at 30 and 35°C. And given the inherent problems with the MBC test (11,12,20) and the fact that, at least with cefamandole against Staphylococcus epidermidis (18), the MBC may not accurately reflect the activity of a specific antibiotic, for selected strains we also performed time-kill rate studies under the four conditions listed above. We found that neither salt supplementation of MHB nor the temperature of incubation influenced the MIC (macrotube) of oxacillin.…”
mentioning
confidence: 99%
“…In the third phenotype, the expression of resistance was also heterogeneous but was increased at 30°C in comparison with that at 37°C (10). Prior studies in our laboratory failed to demonstrate a clear-cut separation of oxacillin-resistant isolates of S. epidermidis into these three resistance phenotypes (29).The objectives of this study were, first, to determine the phenotypes of our isolates of oxacillin-resistant S. aureus and, second, to determine whether these phenotypes correlated with the activity of the cephalosporins cefamandole and cefuroxime against oxacillin-resistant S. aureus when tested at two different temperatures (30 and 35°C) and when the culture medium was supplemented or unsupplemented with NaCl. Our studies utilized oxacillin, rather than methicillin, since oxacillin is recommended for susceptibility testing of staphylococci (17) and is more stable in vitro.…”
mentioning
confidence: 99%